DISTRIBUTION OF Charybdis (Archias) padangensis Leene & Buitendijk, 1952 (CRUSTACEA: DECAPODA: BRACHYURA) IN THE WATERS OF SUMATRA AND JAVA - Hanim, Nisfa; Farajallah, Achmad; Widayat, Kanthi Arum i; Mashar, Ali (Universitas Negeri Medan, 2024)
Until this decade, Charybdis (Archias) padangensis was only from Padang, West Sumatra. It was reported first and the only one in 1952. We obtained several crab samples based on the by-catch from daily fishermen in several locations. Based on morphological identification, we obtained several Charybdis (Archias) padangensis individuals from two locations in Sumatra and one location in Java. The results of this research add to data on the distribution of the species, which was previously only known from the locality type.